1998
DOI: 10.1099/00221287-144-4-937
|View full text |Cite
|
Sign up to set email alerts
|

Physiological function and regulation of flavocytochrome c3, the soluble fumarate reductase from Shewanella putrefaciens NCIMB 400

Abstract: Shewanella putrefaciens produces a soluble flavocytochrome c under anaerobic growth conditions. This protein shares sequence similarity with the catalytic subunits of membrane-bound fumarate reductases from Escherichia coli and other bacteria and the purified protein has fumarate reductase activity. It is shown here that this enzyme, flavocytochrome c 3, is essential for fumarate respiration in vivo since disruption of the chromosomal fccA gene, which encodes flavocytochrome c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 32 publications
0
45
0
1
Order By: Relevance
“…One report indicated that pACYC184 could not replicate in MR-1 (48), but this was subsequently disproven (37). Another report described the use of pJQ200KS to generate a gene replacement knockout of the fumarate reductase of S. putrefaciens (now S. frigidimarina [47]) NCIMB 400 (13). This use cannot be extrapolated to MR-1 because MR-1 maintains pJQ200KS as a free replicon (C. Myers, unpublished data); this is not surprising because it contains the p15A origin of replication from pACYC184 (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One report indicated that pACYC184 could not replicate in MR-1 (48), but this was subsequently disproven (37). Another report described the use of pJQ200KS to generate a gene replacement knockout of the fumarate reductase of S. putrefaciens (now S. frigidimarina [47]) NCIMB 400 (13). This use cannot be extrapolated to MR-1 because MR-1 maintains pJQ200KS as a free replicon (C. Myers, unpublished data); this is not surprising because it contains the p15A origin of replication from pACYC184 (45).…”
Section: Discussionmentioning
confidence: 99%
“…This marked effect on menaquinone levels is of concern because spontaneous Rf r mutants are frequently used as recipients in mating protocols designed to generate mutants. Even though the reduced levels of menaquinones in the Rf r strains (MR-1A and CMTn-1) did not affect the ultimate electron acceptor phenotype of a cymA knockout, effects related to the Rf r phenotype must be considered possible contributing factors to the phenotypes of other Shewanella mutants, e.g., those lacking fumarate reductase (13,35) or MtrB (a putative outer membrane protein required for Fe(III) and Mn(IV) reduction) (4). Even if menaquinone levels are not affected by other rpoB mutations, other as yet uncharacterized effects must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A major heme-stained band at approximately 64-kDa was detected under all growth conditions investigated. This heme-stained band corresponds to the Fcc 3 protein, the soluble, periplasmic, tetraheme flavocytochrome that functions as a physiological respiratory fumarate reductase in Shewanella (8,9). Fcc 3 was the dominant heme-stained band during microaerobic growth or anaerobic growth with fumarate or nitrate as the sole electron acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…The outer membrane cytochromes, including OmcA and OmcB, might be localized where they can make direct contact with extracellular metal oxides at the cell surface. The soluble periplasmic cytochromes could be involved in intermembrane electron transfer between the inner and outer membranes and also in the reduction of soluble Fe(III) chelates that cross the outer membrane (2,5,8).…”
mentioning
confidence: 99%
“…One of these is a 64 kDa tetrahaem¯avo-cytochrome c3, Fcc 3 , which contains bis-Hisligated c 3 -haems and non-covalently bound FAD (Pealing et al, 1995). Fcc 3 has been demonstrated to be the only physiological fumarate reductase present in S. frigidimarina NCIMB400 (Gordon et al, 1998). The sequence of the gene encoding Fcc 3 reveals that this soluble enzyme is related to the catalytic subunit of membrane-bound fumarate reductases from other bacteria (Pealing et al, 1992).…”
Section: Introductionmentioning
confidence: 99%